PERBANDINGAN MODEL PEMBELAJARAN TGT DAN TGT MENGGUNAKAN PERMAINAN BINGO TERHADAP HASIL BELAJAR MATEMATIKA PESERTA DIDIK - Manapa, Imanuel Yosafat Hadi; Mautang, Desi Cetrin (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2024)
The aim of this research is to compare the learning outcomes of students' mathematics learning models taught using the TGT learning model and the TGT learning model using the bingo game as media. This research conducted by quantitative experimental research. The subjects in this research were all class IV students at SD GMIT 01 Kalabahi, totaling 50 students, who were obtained using a saturated sampling technique. The students were divided into two population groups, namely the control and experimental class populations, each consisting of 25 students. The sampling technique used was saturated sampling. Data analysis used in this research is normality, homogeneity test and t test on two unpaired samples. The research results showed that the average value for the control class was 64.27, while for the experimental class it was 80.40. the results of hypothesis testing using the t test on two unpaired samples, obtained a value of t = 17.52 with t table = 1.64. Thus, it can be concluded that the TGT learning model using bingo game media is better than without using it.